Numerical study of the effect of changing tube pitches on heat and flow characteristics from tube bundles in cross flow (2019)
Tube bundles are found in various heat transfer equipment for thermal energy transfer between fluids. However, the inter-spatial arrangement of the tubes of any tube bundle is a determining factor for its thermal and hydraulic performance. In this paper, the effect of varying the transverse and longitudinal pitches downstream staggered circular tube bundle on the heat transfer and flow characteristic was numerically analyzed. Seven variations of tube arrangements were studied by changing the tube pitches within a Reynolds number range of 7 381 to 22 214. The analyses were carried out using the k-ε equation model imposed with the realizability constraint and were solved with finite volume CFD code, COMSOL Multiphysics. The results obtained were found to be in good agreement with existing correlations. The tube bundles with decreasing pitches demonstrated better heat transfer performance while those with increasing pitches exhibited a lower friction factor. Thus, the best thermal-hydraulic performance was obtained from increasing pitch arrangements.